Analysis of Business Capital, Labor, Number of Consumers and Production on SMEs Income in Medan Petisah District - Muhamad Toyib Daulay; Annisa Sanny (Universitas 17 Agustus 1945 Semarang, 2023)
The effect of the independent variable on the dependent variable, which is entitled